2012
DOI: 10.3390/nu4111664
|View full text |Cite
|
Sign up to set email alerts
|

Insulinotropic and Muscle Protein Synthetic Effects of Branched-Chain Amino Acids: Potential Therapy for Type 2 Diabetes and Sarcopenia

Abstract: The loss of muscle mass and strength with aging (i.e., sarcopenia) has a negative effect on functional independence and overall quality of life. One main contributing factor to sarcopenia is the reduced ability to increase skeletal muscle protein synthesis in response to habitual feeding, possibly due to a reduction in postprandial insulin release and an increase in insulin resistance. Branched-chain amino acids (BCAA), primarily leucine, increases the activation of pathways involved in muscle protein synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 102 publications
1
49
1
4
Order By: Relevance
“…Volek et al (2013) provides evidence that humans fed protein (e.g., whey protein) containing a higher proportion of leucine will result in an elevation of blood leucine concentration and stimulate muscle protein synthesis and this may lead to greater gains in muscle mass over time; however, others do not support this linear association between elevated leucine and enhanced muscle protein synthesis (Churchward-Venne et al, 2012). In addition, changes in muscle protein synthesis are relatively small unless sufficient EAA are provided (Manders et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Volek et al (2013) provides evidence that humans fed protein (e.g., whey protein) containing a higher proportion of leucine will result in an elevation of blood leucine concentration and stimulate muscle protein synthesis and this may lead to greater gains in muscle mass over time; however, others do not support this linear association between elevated leucine and enhanced muscle protein synthesis (Churchward-Venne et al, 2012). In addition, changes in muscle protein synthesis are relatively small unless sufficient EAA are provided (Manders et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated extracellular aminoacidemia following whey protein ingestion is known to enhance skeletal muscle myofibrillar protein synthesis (Bohe et al, 2003;West et al, 2011) which is stimulated primarily by EAAs (Paddon-Jones et al, 2004;Tipton et al, 1999;Volpi et al, 2003) and by the BCAA leucine (Drummond and Rasmussen, 2008). Intravenous administration of BCAAs elevates the phosphorylation and activation of p70S6 kinase and 4E-BP1 (Greiwe et al, 2001); p70S6 kinase and 4E-BP1 which are downstream substrates of the mammalian target of rapamycin (mTOR) pathway (Greiwe et al, 2001;Liu et al, 2006;Manders et al, 2012). Leucine supplementation alone has been shown to directly phosphorylate and activate mTOR (Fujita et al, 2007); however, alterations in the rates of myofibrillar protein synthesis are relatively transient unless EAA are provided in sufficient quantities (Manders et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although a large body of observational studies have examined dietary fat and carbohydrate affecting T2D risk4, relatively few studies have directly investigated the role of dietary protein in relation to T2D risk. Short–term intervention studies have revealed that protein intake positively affects body weight control and promotes insulin secretion in pancreatic β-cells5678. In contrast, large and long-term observational studies generally pointed in the opposite direction relating the effect of protein intake to insulin sensitivity and T2D risk9101112.…”
mentioning
confidence: 99%
“…One of the mechanisms of protein-induced insulin resistance appears to be inhibition of glucose uptake through phosphorylation of downstream factors of the insulin signaling cascade by the translation initiation factor serine-kinase-6-1 (S6K1) (Tremblay et al, 2005). On the other hand, it has been put forward that branched-chain amino acids (BCAA), in particular leucine, may help to counteract "anabolic" resistance" which may increase availability of AA for muscle protein synthesis, 568 reduce muscle protein breakdown, and enhance glucose disposal to help maintain blood glucose homeostasis in T2DM (Manders et al, 2012). Recent data on metabolomic profiling in obese adults have suggested associations between BCAA and future risk of T2DM (Newgard et al, 2009a(Newgard et al, , 2009b, whereas the opposite has been found in youth (Michaliszyn et al, 2012a(Michaliszyn et al, , 2012b.…”
Section: Dietary Protein and Blood Glucose Regulationmentioning
confidence: 99%